VISIBLE VIDEO WATERMARKING USING ADAPTIVE TRANSFORMATION TECHNIQUE - T S Ghouse Basha, Konatham Harini, Mandadapu Jhansi Lakshmi, Neeli Akhila, Nelakurthi Utheja, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Nowadays, digital multimedia content (audio or video) can be copied and stored easily and without loss in fidelity. Therefore, it is important to use some kind of property rights protection system. Digital watermarking technology is a general-purpose technology with a wide variety of possible applications. The technology offers a means of conveying information inside a digital media file (for example, inside a photo, movie, or song). It frequently is used to signal basic identifying information about the specific media file in which it is contained, much like a file header does. Video sequences compressed by modern techniques offer another type of domain, motion vectors. Watermarking in this domain slightly alters length and direction of motion vectors. Further, watermarks for video sequences can be classified by the range of application – e.g., hidden information carried by a watermark can be spread overall frames of the video sequence, then the whole sequence is necessary to retrieve that information, or each frame contains watermark with the same information, then only a single frame should be enough. In one frame, one single element of the watermark can be embedded into one pixel, into a block of pixels or even into the whole frame. In this project we are implementing video watermarking using Desecrate Wavelet Transform (DWT).